Pulsed infrared light therapy does not increase nitric oxide concentration in the blood of patients with type 1 and type 2 diabetes mellitus - Arnall, David Alan; Nelson, Arnold G.; Stambaugh, Laura; Sanz Sevilla, Núria; Cebrià i Iranzo, M. Àngels; López Bueno, Laura; Sanz, Isabel; Arnall, Sheridan B. (Acta diabetologica, 2009)
The purpose of this study was to determine if NO blood concentrations increased acutely following an 8-week course of pulsed infrared light therapy (PILT) which could be linked to an improvement in peripheral protective sensation (PPS) in patients who have profound chronic diabetic peripheral neuropathy. A total of 22 subjects with the diagnosis of type 1 ( N = 2) or type 2 ( N = 20) diabetes participated in the study. PILT was administered to one foot chosen at random with the other foot serving as a within-subject control (no treatment). Patients underwent 24 treatments (3 times/week, for 8 weeks) for 30 min per treatment. Venous blood samples were taken during the last 5 min of treatment from veins in the dorsum of the control and experimental feet and were later analyzed for NO concentration . Contrary to the popular supposition, PILT treatments actually resulted in a significantly ( P < 0.05) decreased concentration of NO. Additionally, there were no significant differences between the treated and untreated feet. Since in individuals where PILT has significantly improved PPS, PILT did not stimulate an increased NO content in the blood, it appears that infrared light improves peripheral protective sensation in patients by a mechanism other than an increased NO production.